Female Violent Deaths in Aydın - Uraz, Nihal; Katkıcı, Ufuk; Erel, Özlem (The Bulletin of Legal Medicine, 2009)
In this study, the data of 144 female who died as a result of a violent incident between 2001-2006 were investigated. Violent deaths constitute 11.2% of all medicolegal deaths. The 72.3% of adult women deaths were related to violence and 27.7% were considered as natural death. Most of the medicolegal investigations were performed in 2006 (28.5%). 42.4% were related to accidents, 25% to suicide and 25% to homicide. The manner of death could not be determined in 7.6% of the cases. In 73.6% of the cases autopsy was carried out and in 26.4 % only a postmortem external examination was performed. Autopsy was performed in all cases with an undetermined cause of death and in homicides. Autopsy was carried out only in 39.3% of accidents and 97.2% of suicides. In conclusion furture evaluations about this topic and related issues might decrease the incidence of violence related female deaths through a concrete plan of action on the basis of documentation.Key words: Violent deaths, woman, forensic medicine, Aydın
Keywords: violent deaths; woman; forensic medicine; Aydın